Penerapan Media Diorama dalam Pembelajaran Organ Gerak Hewan untuk Mengukur Hasil Belajar IPA Siswa - Dwi Oktia Putri; Viktor Pandra; Sujarwo Sujarwo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of science learning outcomes by applying diorama media in learning animal movement organs to measure science learning outcomes for fifth grade students at SD Negeri 41 Lubuklinggau. This type of research is experimental Research. The research population was all fifth grade students at SD Negeri 41 Lubuklinggau City for the 2023/2024 academic year. Sample selection is done by random sampling technique. Sample selection is done by random sampling technique. The sample taken was class V.A, totaling 20 students and taught with diorama media. The research method uses a pre-experimental design. Data collection techniques using tests in the form of essay questions. The data obtained were analyzed using the t-test. Based on the results of research and discussion obtained an average value of 80,67 with learning completeness (90%). The results of the t-test analysis obtained tcount = 5,22 > ttable = 1.73 which shows that the hypothesis Hₒ is rejected and Hₐ is accepted. So it can be concluded that the learning outcomes of class V.A students at SD Negeri 41 Lubuklinggau in the 2023/2024 school year after applying diorama media to learning science were significantly complete. Keywords: Media Dioramas, Learning Outcomes, Science.